2008
DOI: 10.1097/pec.0b013e3181850cb7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Orders for Medication in the Resuscitation Room of a Pediatric Emergency Department

Abstract: A standard designated order form was associated with an increase in completeness and with a decrease in prescribing errors in the resuscitation/trauma room of a pediatric emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Variables associated with making medication errors are illness severity and the training level of the provider 2. Prescribing errors with incorrect dosing are the most common type of errors made by physicians 2,810. The ED has inherent features that place the pediatric patient at higher risk for experiencing adverse drug events.…”
Section: Discussionmentioning
confidence: 99%
“…Variables associated with making medication errors are illness severity and the training level of the provider 2. Prescribing errors with incorrect dosing are the most common type of errors made by physicians 2,810. The ED has inherent features that place the pediatric patient at higher risk for experiencing adverse drug events.…”
Section: Discussionmentioning
confidence: 99%
“…Reduce prescribing errors for all patients Alagha, 30 Broussard, 32 Burmester, 35 Cimino, 1 Cunningham, 39 Dinning, 77 Kozer 2005, 55 Larose, 57 …”
mentioning
confidence: 99%
“…Previous studies have reported medication error varying between 10% and 26.5%, compared with 7.2% in our control group. 2,7,12 The participants in our control group were provided with a card containing appropriate milligrams-per-kilogram doses, which is probably better than memory recall. We noted that although residents were instructed to use clinical aids, there were times when some residents relied on their memory, which could have contributed to errors in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Standardization and preprinted order sheets are a low-cost intervention that has been shown to decrease the risk of errors. 7,25,26 A study found that a standardized volume/weightbased system was associated with a reduction in medication errors compared with use of the Broselow tape during simulated Pediatric Advanced Life Support scenarios. 27 A color-coded, prefilled syringe reduced critical dosing errors by emergency physician and nursing teams during simulated pediatric ED resuscitations.…”
Section: Discussionmentioning
confidence: 99%